Protection Against XY Gonadal Sex Reversal by a Variant Region on Mouse Chromosome 13. Issue 2 (1st February 2020) - Livermore, Catherine; Simon, Michelle; Reeves, Richard; Stévant, Isabelle; Nef, Serge; Pope, Madeleine; Mallon, Ann-Marie; Wells, Sara; Warr, Nick; Greenfield, Andy
Abstract: XY C57BL/6J (B6) mice harboring a Mus musculus domesticus -type Y chromosome (Y POS ), known as B6.Y POS mice, commonly undergo gonadal sex reversal and develop as phenotypic females. In a minority of cases, B6.Y POS males are identified and a proportion of these are fertile. This phenotypic variability on a congenic B6 background has puzzled geneticists for decades. Recently, a B6.Y POS colony was shown to carry a non-B6-derived region of chromosome 11 that protected against B6.Y POS sex reversal. Here. we show that a B6.Y POS colony bred and archived at the MRC Harwell Institute lacks the chromosome 11 modifier but instead harbors an ∼37 Mb region containing non-B6-derived segments on chromosome 13. This region, which we call Mod13, protects against B6.Y POS sex reversal in a proportion of heterozygous animals through its positive and negative effects on gene expression during primary sex determination. We discuss Mod13 's influence on the testis determination process and its possible origin in light of sequence similarities to that region in other mouse genomes. Our data reveal that the B6.Y POS sex reversal phenomenon is genetically complex and the explanation of observed phenotypic variability is likely dependent on the breeding history of any local colony.